(3CNHGQ aN hjMji Hf YHO Gddgs - (3CHh RjO CMeO Hf Sgjd GdQGRj,J (B322 (3g` s ((3CMeO Hf fGUQ GdSeGhi GdQfOi GdgGhOi s)
(3ChdgG (B:s
(3GdMeO ddg bGd CHh YHO Gddg GdQGRi hHYO aEfi EfeG EHJOCJ HPcQ GdMSjf Hf Ydi Hf GdMSf GdebJhd HaN dCf Chd MQcJg jMji Hf YHO Gddg s
(3BNQgG (B:s
(3hbO CNHQfi CMeO fH YHO Gddg Hf eMeO aQHkG ef gPG , EdG Cffi COYi dNHQ CHj dGLGQO hef NHQ eMeO Je MOjK GdMSjf Hf Ydi UGMH aN s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ dYeQ Hf eMSf Hf eZdSs
(3fSNI eUMMI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdJGQjNs